2020
DOI: 10.1371/journal.pone.0243295
|View full text |Cite
|
Sign up to set email alerts
|

Polish is quantitatively different on quartzite flakes used on different worked materials

Abstract: Metrology has been successfully used in the last decade to quantify use-wear on stone tools. Such techniques have been mostly applied to fine-grained rocks (chert), while studies on coarse-grained raw materials have been relatively infrequent. In this study, confocal microscopy was employed to investigate polished surfaces on a coarse-grained lithology, quartzite. Wear originating from contact with five different worked materials were classified in a data-driven approach using machine learning. Two different c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 79 publications
0
17
0
1
Order By: Relevance
“…Already over 30 years ago, several scholars, using different methodologies, demonstrated that polish generated by diverse worked materials could be quantitatively discriminated [ 21 – 24 , 28 , 41 – 44 ]. During the last decade, confocal microscopy and texture analysis have been used for the same aim, showing the great potential of this methodology [ 30 , 31 , 5 – 47 ] for tools made with different rocks, including non-homogeneous ones, like quartzite [ 48 ]. Confocal microscopy has taken this approach one step forward, as it is a precise and easy-to-use method for the analysis of textures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Already over 30 years ago, several scholars, using different methodologies, demonstrated that polish generated by diverse worked materials could be quantitatively discriminated [ 21 – 24 , 28 , 41 – 44 ]. During the last decade, confocal microscopy and texture analysis have been used for the same aim, showing the great potential of this methodology [ 30 , 31 , 5 – 47 ] for tools made with different rocks, including non-homogeneous ones, like quartzite [ 48 ]. Confocal microscopy has taken this approach one step forward, as it is a precise and easy-to-use method for the analysis of textures.…”
Section: Discussionmentioning
confidence: 99%
“…Use-wear from different worked materials (plant, animal) [ 37 , 39 , 41 ] and on different raw -materials (flint, pottery, bones, etc.) [ 35 , 48 , 49 , 51 , 52 ] are tested and gradually included in this field of study. All these pilot studies will build a consensus on practices to be followed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The problem is manifold: not all polishes are equally easy to see and interpret, and not all types of data deliver the same answers. Some types of materials, such as cereals [9,10] or antler, bone, and ivory (ABI) have been identified consistently in blind tests or have been separated quantitatively in experimental settings with varying degrees of success (see [11][12][13][14][15]). Traces left by others, especially by soft and elastic materials, such as meat, tendons, etc., are less identifiable [16].…”
Section: Introductionmentioning
confidence: 99%
“…By maximizing the differences, masks might also improve the number of correctly classified types of wear by machine learning algorithms. Recent studies provided mixed results of classification of contact material 29 , 32 , 33 . In these studies, good classifications are often under 70%.…”
Section: Discussionmentioning
confidence: 99%